1992
DOI: 10.1002/ppul.1950130209
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency jet ventilation and surfactant treatment of newborns with severe respiratory failure

Abstract: Twenty-eight newborn infants (birthweight, 2.4 +/- 1.1 kg; gestational age, 34.6 +/- 6.1 weeks) with respiratory distress syndrome (RDS), meconium aspiration syndrome, or pneumonia who deteriorated in spite of optimal conventional mechanical ventilation (CMV) and exogenous surfactant therapy were treated with high-frequency jet ventilation (HFJV) and continued surfactant therapy. For enrollment, infants had to have a limited response to surfactant therapy and conventional ventilation, and meet clinical criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…For example, studies indicate that the distribution and/or efficacy of instilled exogenous surfactant can be improved by jet ventilation [161,162] and partial liquid ventilation [163][164][165]. Additional mechanism-based research on the impact of specific ventilation methods and strategies on the delivery, distribution, and efficacy of exogenous surfactants may be important for optimizing this therapy in ALI/ARDS.…”
Section: Delivery Methods and Dosages For Exogenous Surfactant Therapmentioning
confidence: 99%
“…For example, studies indicate that the distribution and/or efficacy of instilled exogenous surfactant can be improved by jet ventilation [161,162] and partial liquid ventilation [163][164][165]. Additional mechanism-based research on the impact of specific ventilation methods and strategies on the delivery, distribution, and efficacy of exogenous surfactants may be important for optimizing this therapy in ALI/ARDS.…”
Section: Delivery Methods and Dosages For Exogenous Surfactant Therapmentioning
confidence: 99%
“…This variability in response to exogenous surfactant could be secondary to the timing of surfactant administration or to the preparation of surfactant used. Davis and colleagues 77 have observed improved oxygenation and ventilation in a small group of infants with MAS who were treated with a combination of high-frequency jet ventilation and calf lung surfactant extract replacement after deterioration in respiratory status while receiving conventional mechanical ventilation and exogenous surfactant therapy. The importance of surfactant function in infants with MAS has been partly elucidated by Bui et al 78 who demonstrated a dramatic increase in phospholipid, disaturated phosphatidylcholine, and SP-A levels in the tracheal aspirate of infants on extracorporeal membrane oxygenation for respiratory failure just before the cessation of oxygenation.…”
Section: Mas and Surfactantmentioning
confidence: 99%
“…Several investigators have the total protein level and surface tension. Surfactant reported anecdotal experience with surfactant therapy in therapy resulted in elevation of airway phospholipid lev-human neonates with severe MAS (6,7,12). In these els but no decrease of the surface tension.…”
Section: Resultsmentioning
confidence: 99%
“…hypertension with either hyperreactive or remodeled pulmonary vasculature (increased muscular wall thickness) (15). Furthermore, we treated early in the course of the disorder (1 h after meconium), whereas human infants have been treated at 24-48 h of age (6,7,12). The nature of the disorder may be very different after that amount of time and may be responsive to surfactant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation